Global Behavior of a Higher-Order Difference Equation - Tuo Li; Xiu-Mei Jia (Discrete Dynamics in Nature and Society)
This paper is concerned with the global behavior of higher-order difference equation of the form 𝑦𝑛+1=(𝑦𝑛∑exp(𝛽(1−2𝑘𝑖=0𝑎𝑖𝑦𝑛−𝑖)))/(1−𝑦𝑛+𝑦𝑛∑exp(𝛽(1−2𝑘𝑖=0𝑎𝑖𝑦𝑛−𝑖))), 𝑛=0,1,2…, 𝑦−𝑘,𝑦−𝑘+1,…,𝑦0∈(0,1). Under some certain assumptions, it is proved that the positive equilibrium is globally asymptotical stable.